Economic Inequality and Cardiovascular disease in the United Kingdom: A new benchmark and a web dashboard - Lane, Håkan; Sebat, Dalia; Alsen, Fredrik; Magtibay, Pamela (Journal of Global Medicine, 2025)
This paper examines the disparities in heart disease prevalence among different income groups in the United Kingdom, highlighting significant inequalities that persist within the healthcare system. Utilising a specialised Gini index tailored for health inequality, we quantify the extent of these disparities, providing a robust statistical framework for understanding the relationship between socioeconomic status and heart disease outcomes. Our analysis reveals that lower-income groups experience a disproportionately higher burden of heart disease, underscoring the urgent need for targeted public health interventions. To enhance public awareness and accessibility of health equity data, we developed an interactive web dashboard that visualises the prevalence of heart disease across income brackets, allowing users to explore and comprehend the health inequities affecting their communities. This dashboard serves as a vital tool for policymakers, healthcare providers, and the general public, fostering informed discussions and driving efforts toward reducing health inequalities in the UK. Through this work, we aim to contribute to the ongoing dialogue around health equity and advocate for policies that address the root causes of health disparities.